Strategy In Development Of Processing Salak At Ud. Salacca Through Business Model Canvas Approach - Juni Hartati; Yulia Windi Tanjung; Anugrah Sri Widiasyih; Timbul Rasoki (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2019)
This study is aimed to analyze business model, internal external environment and formulate alternative strategies in UD. Salacca based on Business Model Canvas. The methods of research used are descriptive qualitative method. The data was obtained through secondary data and primary data. Data collected through depth interviews, observation and focus group discussion. The sampling method used was purposive sampling. Data were analyzed using the SWOT and BMC. The results showed that SWOT has Strengths (S), South Tapanuli is the salak production center in North Sumatra. Weaknesses (W) such as some products are not always available and cannot meet large-scale demand or exports; venture capital, technology and labor are still limited; there is no official cooperation contract with suppliers, customers and distributors. Therefore, BMC now needs to be improved by utilizing Opportunities (O) including the assistance from the Government in the form of counseling, training and mentoring of the production machinery business; product promotion facilities at trade shows / festivals and also trade sites; other than that the product has been in demand by domestic and foreign tourists; The business already has a link to export products. So as to be able to face the Threat (T) of many competing products that use substitute raw materials and more sophisticated production technology resulting in consumers not loyal. The resulting alternative strategies are increasing consumer reach and business scale; improvement of production facilities and infrastructure; improving services with consumers; partnerships with distributors and souvenir vendors; increase capital, technology and labor.